The Influence Of Sharia Financial Literacy, Islamic Branding And Religiosity On Students' Decisions In Using Sharia Banking Services (Case Study of PBS and MBS UMSU Students) - Salsabila Siregar (Integrasi: Jurnal Studi Islam dan Humaniora, 2023)
The aim of this research is to analyze the influence of sharia financial literacy, Islamic branding and religiosity on students' decisions to use sharia banking services among PBS and MBS UMSU students. The research approach in this thesis is a quantitative approach and the data used is primary data. The population used in this research was students of Sharia Banking and Sharia Business Management at the Muhammadiyah University of North Sumatra, namely 335 students, and the sampling technique used the Slovin formula with a sample size of 182 students. Data analysis techniques using descriptive tests, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The data processing uses the SPSS version 22.0 program.